The Moral Economy of the Capitalist Crowd: Utopianism, the Reality of Society, and the Market as a Morally Instituted Process in Karl Polanyi’s The Great Transformation - Somers, Margaret R. (Humanity: An International Journal of Human Rights, Humanitarianism, and Development, 2020)
In an age of egregious inequality and rising authoritarian, many call for a new “moral economy” and turn to Karl Polanyi’s The Great Transformation for inspiration. Yet Polanyi’s great insight is that those who cannot reckon with the moral economy of “market justice”—the claim that market outcomes, however unequal, are morally just—fail to understand the power of capitalism. Justified by its original claim to rest on natural science, market justice laid the predicate for democracy as mortal threat. Polanyi reveals market justice as based not on natural law but on predistributive political power, and builds his democratic socialist vision on the “reality of society.”
Keywords: market justice; moral economy

Polanyi’s democratic socialist vision: Piketty through the lens of Polanyi - Somers, Margaret R.; Block, Fred (Karl Polanyi and twenty-first-century capitalism, 2020)
This chapter brings Karl Polanyi into dialogue with Thomas Piketty, author of Capital in the Twenty-First Century. The dialogue is intended to make visible key aspects of Polanyi’s theoretical framework while also suggesting limitations in Piketty’s approach to political economy. Specifically, the authors use the concept of ‘predistribution’ – implicit in Polanyi – to critique Piketty’s emphasis on redistribution as the solution to growing wealth and income inequality. Predistribution conveys the idea that the initial market distribution of income is not natural but is shaped by the systematic exercise of political and economic power.